Pharmaceutical support in liver transplantation at a reference center in Rio Grande do Sul - Pranke, Mariana de Andrade; Zanotelli, Maria Lúcia; Fleck Jr., Alfeu; Brandão, Ajácio; Marroni, Cláudio; Cantisani, Guido (Brazilian Journal of Transplantation, 2017)
The introduction of the everolimus as immunosuppressant in the liver transplantation has been shown to be safe and effective in the prophylaxis and preservation of the renal function. Prospective follow-up and chart analysis of liver transplant patients treated with everolimus was performed. Purpose: To highlight the importance of the pharmacist in transplantation centers. Method: Along the study, 93 patients were included, being 72 under active treatment. The successful treatment depends on the multidisciplinary follow-up, and it is extremely important the involvement of the patient, making him to become positive and an active part of the treatment. Results: The most frequent problems were: patients cutting the everolimus tablet, late SL after dose adjustment, lack of adhesion to the collection, and serum level collection out of time. Discussion: Upon the introduction of new drugs, it is required to observe possible adverse events further to ensure that the patient correctly follows the treatment. Conclusion: The presence of the pharmacist in the transplantation center allows the patient to get a reference to clarify doubts on the proper use of immunosuppressant.